A National Survey of Obstetrics and Gynecology Emergency Training and Deficits in Office Emergency Preparation [A53]. (May 2022) - Maciejko, Laura; Cope, Adela; Mara, Kristin; Bell, Shannon L.; Green, Isabel
Abstract : INTRODUCTION: While rare, emergencies encountered during office procedures have the potential for significant morbidity if the team is caught unprepared. The aim of this study was to evaluate current availability of and needs for training in office emergencies in residency programs in the United States. METHODS: This was a cross-sectional survey of residents from accredited obstetrics and gynecology residency programs. Identified programs were those with representation in the American College of Obstetricians and Gynecologists Simulation Working Group (ACOG SWG). A multi-item instrument was developed, designed, and edited by representatives of the ACOG SWG for accuracy and content validity. Participants were asked to rate their level of agreement with statements on importance of training in the recognition and management of obstetrics and gynecology emergencies and their confidence in management of those emergencies. Specific emergencies encountered in the office, gynecologic surgery, and obstetrics were queried. RESULTS: Six programs participated for a total of 116 residents and a response rate of 62% (116/188). Most residents agreed office emergency (97.5%) and obstetric emergency training (94.8%) were important in residency training. While 65.5% were confident in managing a vasovagal episode in the office, 0.9% were confident in managing lidocaine toxicity. In contrast, the majority of residents felt confident in obstetric emergency management across all listed emergencies (hemorrhage, cord prolapse, shoulder dystocia, eclampsia). CONCLUSION: While rated as important to residency training, significant gaps exist within resident preparation for identification and management of office-based emergencies, providing an opportunity for curriculum development and education.